Laboratory study of iron isotope fractionation during dissolution of mineral dust and industrial ash in simulated cloud water. (July 2022) - Maters, Elena C.; Mulholland, Daniel S.; Flament, Pascal; de Jong, Jeroen; Mattielli, Nadine; Deboudt, Karine; Dhont, Guillaume; Bychkov, Eugène
Abstract: Atmospheric deposition is a key mode of iron (Fe) input to ocean regions where low concentrations of this micronutrient limit marine primary production. Various natural particles (e.g., mineral dust, volcanic ash) and anthropogenic particles (e.g., from industrial processes, biomass burning) can deliver Fe to the ocean, and assessment of their relative importance in supplying Fe to seawater requires knowledge of both their deposition flux and their Fe solubility (a proxy for Fe bioavailability). Iron isotope ( 54 Fe, 56 Fe, 57 Fe, 58 Fe) analysis is a potential tool for tracing natural and anthropogenic Fe inputs to the ocean. However, it remains uncertain how the distinct Fe isotopic signatures (δ 56 Fe) of these particles may be modified by physicochemical processes (e.g., acidification, photochemistry, condensation-evaporation cycles) that are known to enhance Fe solubility during atmospheric transport. In this experimental study, we measure changes over time in both Fe solubility and δ 56 Fe of a Tunisian soil dust and an Fe–Mn alloy factory industrial ash exposed under irradiation to a pH 2 solution containing oxalic acid, the most widespread organic complexing agent in cloud- and rainwater. The Fe released per unit surface area of the ash (∼1460 μg Fe m −2 ) is ∼40 times higher than that released by the dust after 60 min in solution. Isotopic fractionation is also observed, to a greater extent in the dust than the ash, in parallel with dissolution of the solid particles and driven by preferential release of 54 Fe into solution. After the initial release of 54 Fe, the re-adsorption of A-type Fe-oxalate ternary complexes on the most stable surface sites of the solid particles seems to impair the release of the heavier Fe isotopes, maintaining a relative enrichment in the light Fe isotope in solution over time. These findings provide new insights on Fe mobilisation and isotopic fractionation in mineral dust and industrial ash during atmospheric processing, with potential implications for ultimately improving the tracing of natural versus anthropogenic contributions of soluble Fe to the ocean. Graphical abstract: Image 1 Highlights: Fe solubility and isotopic fractionation of dust and ash are investigated during simulated atmospheric processing. The Fe solubility is 40 times higher in the ash than in the dust. An isotope fractionation is observed, with preferential release of soluble 54 Fe, to a greater extent for the dust than ash. Re-adsorption of Fe-oxalate complexes compete with the release of soluble Fe, which maintain a 54 Fe enrichment in solution.